1989
DOI: 10.1088/0029-5515/29/4/001
|View full text |Cite
|
Sign up to set email alerts
|

Electron thermal confinement studies with applied resonant fields on TEXT

Abstract: Externally applied magnetic fields are used on the Texas Experimental Tokamak (TEXT) to study the possibility of controlling the particle, impurity and heat fluxes at the plasma edge. Fields with toroidal mode number n = 2 or 3 and multiple poloidal mode numbers m (dominantly m = 7) are used, with a poloidally and toroidally averaged ratio of radial to toroidal field components 〈|br/Bø〉 ≅0. 1%. Calculations show that it is possible to produce mixed islands and stochastic regions at the plasma edge (r/a ≥ 0.8) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
61
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 42 publications
11
61
0
1
Order By: Relevance
“…The ergodic limiter consists of a grid-shaped coil wound around the tokamak vessel and conducting a current that generates these disturbing fields. This claim is supported by theoretical as well as experimental evidences [6].…”
Section: Introductionsupporting
confidence: 54%
“…The ergodic limiter consists of a grid-shaped coil wound around the tokamak vessel and conducting a current that generates these disturbing fields. This claim is supported by theoretical as well as experimental evidences [6].…”
Section: Introductionsupporting
confidence: 54%
“…However, a systematic investigation of the turbulence properties, such as frequency and wave-number spectra and the fluctuation propagations, has not been made or was done for a reduced set of wavenumber values [5]. A distinct description in the ergodic and laminar zones was also not given.Recently, on the tokamak TEXTOR the Dynamic Ergodic Divertor (DED) [4] has been installed at the high-field side of the torus (R=a 1:75=0:47 m), contrary to other machines where the ED coils were mounted at the low-field side [1][2][3]. The DED consists of 16 perturbation coils oriented parallel to the field lines on the magnetic flux surface with a safety factor q 3.…”
mentioning
confidence: 99%
“…Results on the tokamaks TEXT [1], Tore Supra [2], DIII-D [3], and TEXTOR [4] have demonstrated that an ergodized magnetic boundary can be effective to optimize the plasma-wall interaction. Meanwhile, the local effects of the magnetic ergodization on edge turbulence and turbulent cross-field transport have also been studied both experimentally [1,5,6] and theoretically [7,8].…”
mentioning
confidence: 99%
See 2 more Smart Citations